Politics in Socrates' Alcibiades: A Philosophical Account of Plato’s Dialogue Alcibiades Major - Archie, Andre (Springer, 2015)
This volume provides the first full, political and philosophically rigorous account of Plato’s dialogue Alcibiades Major. The book argues that Alcibiades Major accomplishes its goal, which is to redirect Alcibiades’ political ambitions, not by arguing for specific propositions based on specific premises. The dialogue accomplishes its goal by generalizing the notion of argument to include appeals to Alcibiades’ doxastic attitudes toward his ability and knowledge to become a powerful ruler of the Greek people.